A Critical Review of the Book Women in Mongol Iran: The Khatuns, 1206-1335 - Yazdan Farrokhi (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Research on the situation of women during the Mongol rule, due to the different views that the Mongols had about the position of women in politics and society, is one of the important fields of research on the history of Iran that has attracted the attention of some scholars. However, despite the importance of this field, compared to other fields, a small number of coherent and problem-oriented research in this field has been done and published. Therefore, the publication of the book Women in Mongol Iran, which was originally the author's doctoral dissertation, deserves to be introduced, reviewed, and evaluated. The author claims that he has addressed this issue due to the lack of in-depth study in this important field, and therefore, this article seeks to evaluate the achievement of this aim in this book. The present article, in a descriptive-analytical method and with a critical approach, addresses the question: to what extent has the author's achievements been able to achieve a fundamental and deep understanding of women in Mongol Iran? It seems that the author has been successful in achieving his specific goals and, in addition to some content and form, has provided a solid achievement and foundation for further research in this field.